Politics of Participatory Culture: Indonesian NCTzen and WayZenNi Transforming Fandom for #SM_BOYCOTT_GENOCIDE - Nadya Ulfa; Desi Dwi Prianti (Universitas Brawijaya, 2025)
This study examines the #SM_BOYCOTT_GENOCIDE movement as a form of strategic activism undertaken by Indonesian NCTzen and WayZenNi to respond to the dilemma between affective bonds and a sense of humanity. Using Henry Jenkins' framework of fan activism, this study analyzes how participatory culture practices are repurposed as instruments of political participation. Through digital ethnography, data were collected from social media archives (X, Instagram, TikTok, Weverse), interviews with eight fans, and participant observation. The findings suggest this movement is more than a simple act of rejection. It functions as a communicative strategy that balances two distinct approaches: exerting pressure through boycotts and protests and persuading through educational efforts rooted in humanitarian values and often framed by religious narratives. Fandom can take over commodified relational spaces like Weverse, Bubble, and fan call sessions, transforming them into arenas for political struggle. This demonstrates that fans are not just passive consumers but are socio-political actors who can strategically balance affection and ethical commitments and turn fandom into a platform for informal civic education.